Django : web development with Python : from an idea to a prototype–a complete guide for web development with the Django framework /: web development with Python : from an idea to a prototype–a complete guide for web development with the Django framework. (2016) - Dauzon, Samuel; Bendoraitis, Aidas; Ravindran, Arun
No abstract available